Evolutionary history of campo rupestre: an approach for conservation of woody plant communities - Pontara, Vanessa; Bueno, Marcelo Leandro; Rezende, Vanessa Leite; de Oliveira-Filho, Ary Teixeira; Gastauer, Markus; Meira-Neto, João Augusto Alves (Biodiversity and conservation, 2018)
The campo rupestre sensu lato is among the most species-rich vegetation in the world, harbouring a high proportion of endemic species. We aimed to identify the processes that could generate a high level of phylogenetic diversity (PD) in campo rupestre for woody species and point out biodiversity hotspot areas which may provide additional information for conservation planning. We compiled a database of 2049 woody species from 185 community inventories. We calculated the evolutionary history using species richness (SR), PD, mean pairwise phylogenetic distance between species (MPD), the mean nearest taxon distance (MNTD) and their equivalents standardised (ses.PDss, ses.MPD, ses.MNTD), evolutionary distinctiveness (ED), and biogeographically weighted evolutionary distinctiveness (BED). Cloud dwarf-forests had the highest SR, PD, MPD and ses.MPD and lowest MNTD, while rupestrian cerrado presented the highest ses.PD and ses.MNTD. All areas are important for conservation, but the intersections between the hotspots should receive special attention in future conservation actions. The grids identified as hotspots by three or more metrics were localized mainly in Espinhaço Range in Minas Gerais State and a further expansion of protected areas is required. Moreover, the intersections between the hotspots obtained by mean ED and ses.PD are concentrated in the rocky dwarf forest and rupestrian cerrado, with considerable conservation gaps. The degree of protection of campo rupestre was low with unprotected areas comprising 56% of the species. Our results show an urgent need for increasing protected areas of campo rupestre in order to avoid the loss of valuable, endemic species with unique evolutionary history.